PEMBUATAN ARANG BRIKET DARI SERBUK GERGAJIAN KAYU LIMBAH INDUSTRI PENGOLAHAN KAYU MERBAU - Hermanus Jimy Suripatty; Nicodemus Rahanra; Wardhana Wahyu Dharsono (Jurnal Akrab Juara, 2018)
The waste referred to herein is a by-product formed by the activity of woody biomass or fibrous ligno-cellulose, an unmet raw material. In this case, it is restricted to merbau wood processing industry. The existence of waste referred to the problem of handling that has been left to rot, stacked and burned all of which have negative impact on the environment so that the handling needs to be considered. One way that can be taken is to use it into value-added products with applicative and populist technology so that the results are easily socialized to the public. Evaluation results show some positive prospect as an example of applicative technology can be applied satisfactorily in converting waste wood processing industry into charcoal charcoal, charcoal briquettes, activated charcoal, charcoal compost and soil conditioning. In general, the combustion process of solids consists of several stages of heating, drying, devolatilization and charcoal burning. Factors that determine the combustion characteristics of a briquette are combustion velocity, heating value, specific gravity and the amount of pollution or volatile compound produced. This research uses raw material of merbau sawdust waste with carbonization temperature and adhesive used in research in the form of sago flour. Keywords: Waste, Sawn Timber, Briquettes, Sago Flour, Merbau Wood.